Biochar An Imperative Amendment for Soil and the Environment - Abrol, Vikas; Sharma, Peeyush (IntechOpen, 2019)
This book is intended to provide basic information and an overview of emerging researchable issues related to the use of biochar for mitigating climate change, water scarcity, soil degradation, and food security in a sustainable manner. We have aimed to compile information from diverse sources into a single volume and provide comprehensive information and analysis on biochar production technology and its implications in agriculture. This book represents basic and applied knowledge and acts as a vital tool for scientists, policymakers, and students working for global sustainability.